2013
DOI: 10.1371/journal.pone.0067660
|View full text |Cite
|
Sign up to set email alerts
|

The Bi-Functional Organization of Human Basement Membranes

Abstract: The current basement membrane (BM) model proposes a single-layered extracellular matrix (ECM) sheet that is predominantly composed of laminins, collagen IVs and proteoglycans. The present data show that BM proteins and their domains are asymmetrically organized providing human BMs with side-specific properties: A) isolated human BMs roll up in a side-specific pattern, with the epithelial side facing outward and the stromal side inward. The rolling is independent of the curvature of the tissue from which the BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 53 publications
8
63
0
Order By: Relevance
“…As previous studies have shown that collagen and perlecan act in opposition to regulate the mechanical properties of the basement membrane, determining what other molecular signals or basement membrane components regulate basement membrane pliability will be of interest. Furthermore, recent studies on isolated native basement membranes from adult human tissues have indicated that basement membranes have a distinct sidedness, with the epithelial side of basement membranes having different physical properties and epitope distribution from the stromal side (Halfter et al, 2013). The unique characteristics on each side of the basement membrane appear to be functionally relevant, as epithelial cells adhere only to the epithelial side of the basement membrane and not to the stromal side (Halfter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous studies have shown that collagen and perlecan act in opposition to regulate the mechanical properties of the basement membrane, determining what other molecular signals or basement membrane components regulate basement membrane pliability will be of interest. Furthermore, recent studies on isolated native basement membranes from adult human tissues have indicated that basement membranes have a distinct sidedness, with the epithelial side of basement membranes having different physical properties and epitope distribution from the stromal side (Halfter et al, 2013). The unique characteristics on each side of the basement membrane appear to be functionally relevant, as epithelial cells adhere only to the epithelial side of the basement membrane and not to the stromal side (Halfter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies on isolated native basement membranes from adult human tissues have indicated that basement membranes have a distinct sidedness, with the epithelial side of basement membranes having different physical properties and epitope distribution from the stromal side (Halfter et al, 2013). The unique characteristics on each side of the basement membrane appear to be functionally relevant, as epithelial cells adhere only to the epithelial side of the basement membrane and not to the stromal side (Halfter et al, 2013). These studies suggest that there is an intriguing, unexamined complexity that might organize tissue architecture (Halfter and Yip, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, our results seemed difficult to conciliate with a monolayer basement membrane concept. Our recent AFM and cell adhesion analysis of the lens capsule, Descemet's membrane and ILM of 20 human cadaver eyes revealed that the proteins and peptide domains within adult human basement membranes are organized in at least 2 distinct sublayers [81]. This layered distribution provides basement membranes with side-specific properties, including a characteristic tendency to roll in a side-specific pattern.…”
Section: Ilm Materials Properties In Chromovitrectomymentioning
confidence: 99%
“…The problem of direct testing for BM properties has been recently overcome by using adult human BMs for experimentation: adult human BMs are thicker than BMs from shortlived laboratory animals and can be isolated, handled, mounted on glass slides and tested for their composition, their biomechanical properties and their cell adhesion activities (Halfter et al, 2013b). These studies have shown that human as well as non-human BMs are bi-functionally organized with an epithelial side that is characterized by a high abundance of laminin, a high stiffness and a strong cell adhesion-promoting activity.…”
Section: Introductionmentioning
confidence: 99%